Relationships between Attitude and Water Resource Conservation Behavior of Responsible Person for Water Management: A Case Study of 3 Stars - Hotel in Bangkok - Junsuthonpoj, Sumeth (Dusit Thani College Journal, 2020)
The purposes of this research were 1) to examine attitudes of the hotel personnel towards water conservation, 2) to examine behaviors of the hotel personnel towards water conservation, 3) to identify relationships between attitudes and behaviors towards water conservation that affect the differences in hotel sizes. A questionnaire and an in-depth interview were the primary instruments to collect data for this research study. A questionnaire was employed to obtain quantitative data from 135 participants who worked in 3-star hotels in Bangkok; whereas the interviews with the key informants were carried out for qualitative data. In this research, the quantitative data were analyzed with Frequency, Percentage, Mean and Standard Deviation as well as inferential statistics such Pearson product-moment correlation coefficient and One-way Analysis of Variance; while content analysis is applied to the qualitative data. The research findings had led to three conclusions. Firstly, the participants’ attitudes and behaviors towards water conservation were moderately positive. Secondly, the study had suggested a weak correlation between water conservation attitudes and codes of practice as well as between water conservation behaviors and codes of practice. Most importantly, from comparing the various sizes of hotels in which the participants work, the size of hotel played insignificant role at the 0.05 level in shaping the participant’s attitudes, behaviors and codes of practice towards water conservation. The interview of water management and conservation participant in hotel recommended that government must have a seriously support for the strategy and development mechanism to grow the appropriate attitude for 3-star hotels. Thus, 3-star hotels have limitation in terms of specialist and fund for water conservative training which can perform a high performance water conservation along with the sustainable development.